The overnight rate of interest under averaged reserve requirements: Some theoretical aspects and the Finnish experience - Tuomas Välimäki (Bank of Finland, 1998)
Averaging the reserve requirement is often considered an efficient way to reduce volatility at the very short end of the money market yield curve.The Bank of Finland began to apply an averaging provision at the beginning of October 1995.Notably, the volatility of the overnight rate of interest in the Finnish money markets has increased since the start of the averaging scheme.This paper builds up a simple model of the determination of the overnight rate of interest.The effects of both the averaging scheme and the central bank's reaction to the bids it receives in money market tenders are evaluated against the model.The paper ends with an evaluation of the empirical evidence from the first two years that have passed since the introduction of the averaging provision in Finland.
URN:NBN:fi:bof-20140807515
Keywords: 330; money market tenders; minimum reserves; liquidity; averaging; convexity; interest rate volatility